Knowledge, attitudes and practices of healthcare professionals toward the novel coronavirus during the early stage of COVID-19 in a lower-and-middle income country, Bangladesh - Patwary, Muhammad Mainuddin; Hossain, Md. Riad; Sultana, Rabeya; Dazhamyar, Ahmad Riaz; Parsa, Ali Davod; Kabir, Russell; Shoib, Sheikh (Frontiers in Public Health, 2022)
Healthcare workers (HCWs) are at an increased risk of COVID-19 infection because of their direct exposure to suspected and confirmed coronavirus patients in healthcare facilities. This condition is even more acute in low-and lower-middle-income countries (LMICs). Given the poor healthcare settings of Bangladesh, it is challenging to halt the spread of infection without proper knowledge, attitudes, and good behavioral practices (KAPs). Therefore, this study conducted a cross-sectional study from May 5 to 31, 2020, with 203 healthcare professionals to determine the knowledge, attitudes, and practices (KAP) toward COVID-19. Participants were doctors, nurses, dentists, and allied health professionals. A self-administered questionnaire including several KAP-related items aligned with the World Health Organization (WHO) guidelines was distributed over various online platforms to collect data. Bivariate and multivariable logistic regression analyses were conducted to determine the factors influencing KAP levels. The majority of participants were male (52.22%). The prevalence of high knowledge levels, positive attitudes, and good practices were 51.23, 45.81, and 49.75%, respectively. Social media was the most common source for seeking coronavirus information. Workers at private institutions were less likely (OR = 0.56, 95% CI = 0.30–0.95, p < 0.05) to be knowledgeable than workers at public institutions. Doctors had more positive attitudes than other healthcare professionals. Older participants showed high rates of good behavioral practices (OR = 1.05, 95% CI = 1.06–1.32, p < 0.05) than younger ones. Workers at private institutions had a better practice level toward COVID-19 (OR = 2.11, 95% CI = 1.17–3.83) than those at public institutions. These results point to the necessity for proper training programs for medical professionals that help them gain confidence to deliver the correct treatment to their patients and the need to implement preventative steps during pandemics.